The effect of using plyometric exercises in my circular style and stations in developing explosive power and scoring skill among the players of the Misan - Zainab Abdel Hassan Hadab Amer ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The development in the sports field and the emphasis on the use of modern training methods in the field of futsal for futsal to develop the physical capabilities of female players to reach advanced levels through the use of plyometric exercises in two training methods (circular training method and station training method) in developing explosive power and scoring in football. The research problem focused With the lack of interest of the trainers in giving plyometric exercises during the training units, despite the fact that it develops the characteristic of explosive power, which is of great importance to the five-a-side football player in performing a level of correction distinguished by accuracy and speed, which depends on it in determining the results of the matches. The research aims to identify the effect of using exercises. Plyometric in the development of explosive power and shooting in football for the halls among the members of the research sample, as well as identifying which of the two methods, circular or stations, is better in developing explosive power and the skill of scoring in football for the halls among the members of the research sample. As for the two hypotheses of the research, there are no significant differences between the use of plyometric exercises with my method (circular and stations) in developing explosive power and scoring in football between the pre and post tests and in favor of the post tests. Football scoring